One Step Nucleic Acid Amplification (OSNA) positive micrometastases and additional histopathological NSLN metastases: Results from a single institution over 53 months. Issue 2 (April 2016) - Babar, M.; Madani, R.; Jackson, P.; Layer, G.T.; Kissin, M.W.; Irvine, T.E.
Abstract: Introduction: The role of sentinel lymph node micrometastases on histopathological analysis is controversial in axillary staging and management in clinically node negative breast cancer. Long-term studies addressing the clinical relevance of occult breast cancer in sentinel lymph nodes based on molecular analysis are lacking. One Step Nucleic Acid Amplification (OSNA), a highly sensitive assay of cytokeratin 19 mRNA, is used intra-operatively for the detection of lymph node macro- and micrometastases in breast cancer. Aim: The aim of this study is to review the rate of micrometastases and further histopathological NSLN metastases, in our unit following the introduction of OSNA in Guildford. Methods: Data was collected prospectively from the period of introduction 01/12/2008 to 31/05/2013. All patients eligible for sentinel lymph node biopsy were offered OSNA and operations were performed by the consultant breast surgeons. Presence or absence of micro-metastases depends on the agreed cut-off point on the amplification curve. On detection of micrometastases (+) and positive but inhibited (i+) metastases, a level 1 axillary clearance (ANC) was performed and for a macrometastasis (++), a level 3 ANC was carried out. Results: 66% of the patients had negative SLN ( n = 672) and 34% ( n = 336) had positive sentinel lymph nodes who had further axillary surgery. Of these, 45% ( n = 152/336) had macrometastases, 40% ( n = 136/336) had micrometastases and 15% (48/336) had positive but inhibited results. There was no difference in the patient demographics and tumour characteristics in the various positive SLN groups. In patients with micrometastases, 15% (20/136) had further positive NLSNs and a further 6% (8/136) had >4 overall positive nodes (SLN + NSLN) thus requiring adjuvant supraclavicular/chest wall radiotherapy ( p < 0.05). 25% of node positive patients had further NLSN metastases (85/336) and in these patients, the ratio of positive SLN/harvested SLN (+SLN/SLN) is constant at 1:1. This shows the likelihood of further positive NSLNs if all the harvested lymph nodes are positive. This linear trend is present in both micro-and macrometastases, thus correlating with the size and number of NSLN metastases. Conclusion: Our study reflects the tumour burden of NSLNs based on the molecular analysis of the SLN. OSNA has the potential to accurately identify axillary micrometastases. Micro-metastases are important as some of the patients with micrometastases had overall four positive nodes [SLN + NSLN] (criteria for radiotherapy in the absence of other adverse clinicopathological features). Also, our study highlights certain factors that predict the NSLN metastases, pending validation by further prospective long-term data. This will allow accurate calculation of the axillary tumour burden, particularly in patients with micro-metastases.